Span length effect on flexural properties of composite laminate reinforced with a plain weave carbon fiber fabric in a polymer matrix - Marszałek Jerzy (Science and Engineering of Composite Materials, 2022)
This article focuses on an experimental study of the flexural response of a polymer composite laminate (CL) reinforced with a plain weave carbon fiber fabric. The aim of this research is to investigate the effect of the span length-to-specimen thickness ratio on the flexural properties of the selected CL. The laminate specimens were tested in the three-point flexure configuration for span length-to-specimen thickness ratios of 16, 20, 32, 40 and 60. The investigations were carried out to identify on-axis and 45° off-axis flexural responses of the CL. For this reason, two types of rectangular flat specimens were prepared, differing in reinforcement orientation relative to the support span. Using the special code, the lay-up of the specimens was designated as [(0/90)F]8 and [±45 F]8, respectively. It was found that the flexural modulus and flexural strength of the specimens depend on the span length-to-specimen thickness ratio. Despite testing the same CL, the response of the specimens to the change in the span length is different. In addition, it was concluded that the span length also has a significant influence on the final failure of the laminate specimens.